Analysis of the Influence of Business Legality, Halal Labeling and Promotion on MSME Products in Kwala Serapuh Langkat Village - ,, Erwansyah; Yanti, Eli Delvi; Wahyono, Teguh; Ninda, Via Vio (Universitas Negeri Medan, 2024)
Micro, Small, and Medium Enterprises (MSMEs) have an important role in the local economy, including Kwala Serapuh Village in Langkat. Business legality, halal labeling, and promotion are key factors that can affect the success of MSME products. However, there have not been many studies that have examined the influence of this combination of factors on MSME products in Kwala Serapuh Village. This study aims to analyze the influence of business legality, halal labeling, and promotion on MSME products in Kwala Serapuh Village, Langkat. The sample in this study was 85 respondents. The analysis method used is multiple linear regression analysis. The results of the study show that partially Business Legality (X1) has a significant positive effect on the variable of MSME Products (Y). Halal labeling (X2) has a significant positive effect on the variable of MSME Products (Y). Promotion (X3) had no positive effect and was not significantly significant to the variable of MSME Products (Y). Simultaneously, Business Legality (X1), Halal Labeling (X2) and Promotion (X3) have a significant positive effect on the MSME Product variable (Y) in MSME actors in Kwala Serapuh Village, Lalat Regency.